Land degradation processes and factors affecting crop production in Foothills of Jammu Shivaliks - SHARMA, VIKAS; ARORA, SANJAY (Journal of Soil and Water Conservation, 2021)
Wide scale land degradation of catchments in terms of land, soil and vegetation has been observed in the foothill Himalayas of Jammu region. An attempt was made to identify and relate the factors involved in land degradation. It was found that there exists a continuous cycle of events, involving both natural and anthropogenic factors, promoting land degradation. The weak lithology of the lower Shivaliks consisting of rocks like sandstone, conglomerate, shale, silt stone and limestone are relatively easily weatherable and therefore prone to quick erosion. Sloping relief pattern results in accelerated erosion causing removal of surface material. Surface runoff is higher on sloping lands resulting in lesser percolation of water which is essential for profile development. The high intensity rainfall during monsoon disturbs the top soil, and in turn loosens it, resulting in sheet and rill erosion. Increased population coupled with poverty is putting pressure on land maintenance. Younger generations among the farming community has lesser interest in farming and, therefore, the maintenance of land takes a back seat. Lack of knowledge regarding soil and water conservation measures is another important factor contributing towards land degradation in the area. Only 43 per cent of the farmers in the lower Shivaliks of Jammu are aware about the severity of the problems related to runoff and soil loss. Increased population pressure and smaller land holdings have promoted deforestation leading to unabated soil loss and land degradation. All the above factors lead to continuous land degradation, thereby reducing the productivity of these lands, which in turn affects the economic condition of the farmers luring them to other sources of employment and the cycle continues. The challenge lies in protecting the limited land resource from further degradation, improving productivity of land and eroding poverty in Jammu region of the state.